CISTO PERIAPICAL: REVISÃO - Martins, Anna Karina; Camargo, Ana Júlia; Girelli, Raíssa Alba; Slaviero, Renata; Senger, Franciane Rios; Tomazeli, Karin Berria (Anais de Odontologia / ISSN 2526-9437, 2018)
.